2002
DOI: 10.1080/08958370290084764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subchronic Inhalation Exposure of Rats to Emissions From a Diesel Engine Burning Soybean Oil-Derived Biodiesel Fuel

Abstract: There is increasing interest in diesel fuels derived from plant oils or animal fats ("biodiesel"), but little information on the toxicity of biodiesel emissions other than bacterial mutagenicity. F344 rats were exposed by inhalation 6 h/day, 5 days/wk for 13 wk to 1 of 3 dilutions of emissions from a diesel engine burning 100% soybean oil-derived fuel, or to clean air as controls. Whole emissions were diluted to nominal NO(x) concentrations of 5, 25, or 50 ppm, corresponding to approximately 0.04, 0.2, and 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 45 publications
3
30
0
2
Order By: Relevance
“…The elevated levels of MCP-1 upon B100 exposure, suggesting an increase in the monocyte/macrophage recruitment to the lung ( Figure 3A), are further paralleled by enhanced MPO activity in lung homogenates compared to D100 ( Figure 1A). An infiltration of macrophages in pulmonary tissue during a subchronic exposure of soybean BD CE was also observed previously (Finch et al, 2002;Brito et al, 2010). Further, exposure to organic fractions of diesel exhaust particles was found to elicit a proinflammatory response in human airway epithelial (Bonvallot et al, 2001) and other cells (Fahy et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The elevated levels of MCP-1 upon B100 exposure, suggesting an increase in the monocyte/macrophage recruitment to the lung ( Figure 3A), are further paralleled by enhanced MPO activity in lung homogenates compared to D100 ( Figure 1A). An infiltration of macrophages in pulmonary tissue during a subchronic exposure of soybean BD CE was also observed previously (Finch et al, 2002;Brito et al, 2010). Further, exposure to organic fractions of diesel exhaust particles was found to elicit a proinflammatory response in human airway epithelial (Bonvallot et al, 2001) and other cells (Fahy et al, 1999).…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies on toxicity of BD emissions, other than mutagenicity studies, were performed either in rats over extended time periods (Finch et al, 2002) or in mice involving exposure to 550 μg/m 3 of BD exhaust for only 1 h (Brito et al, 2010). In this study, oxidative stress and inflammatory responses were examined in lung and liver of mice upon inhalation exposure to 50, 150 or 500 μg/m 3 of neat BD (B100) and D (D100) CE, 4 h/d, 5 d/wk, for a total period of 4 wk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Couple this finding to their observation that biodiesel emissions are in the ultrafine PM region and there is a motive for more health effects research. The few cytotoxicity studies on biodiesel SOF have been equivocal [31] but mutagenicity studies demonstrated less mutagenic potency for biodiesel compared to petroleum diesel [15,32]. Biodiesel is the first renewable diesel fuel to show signs of becoming a commercially accepted part of our nation's energy infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Em contrapartida, apenas alguns estudos focam na análise do combustível biodiesel em nível de toxicidade (Finch et al, 2002;Khan et al, 2007;Liu et al, 2008) citotoxicidade e mutagenicidade (Carraro et al, 1997;Bunger et al, 1998Bunger et al, , 2000aBunger et al, , 2000bBunger et al, , 2007 …”
Section: Combustíveis Diesel E Biodieselunclassified